The realization of methods of formation of healthkeeping competence in preschool children in educational process of preschool establishments. (Journal of Educational Sciences, 2016)
The article presents the description of realization of method of formation of healthkeeping competence in preschool children in educational process of preschool establishments. The methodology includes three sections: «Life skills, promote physical health»; «Life skills, promoting social health»; «Life skills that promote mental and spiritual health».It highlights the stages of organization of educational process: stage of motivation, theoretical and practical stages. The article gives the algorithm as for the learning of each topic during the week. It characterizes children and teachers’ activity according to the methods which are given in the methodology. The results of the implementation in the educational process in preschool educational institutions of the methods of formation of health–competence in children of preschool age have confirmed the feasibility of its use. Witnessed a positive impact on the increase children’s interest in learning about health, development of motivation for a healthy life, knowledge, and skills, health, ensuring the practical application of life skills that promote physical, social, mental and spiritual health.
Keywords: preschool children; healthkeeping competence; methodology; stages of organization of education; methods